1990
DOI: 10.1128/aac.34.11.2075
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among respiratory isolates of Haemophilus influenzae, Moraxella catarrhalis, and Streptococcus pneumoniae in the United States

Abstract: A national surveillance study was conducted to determine trends in antimicrobial resistance patterns among three common causes of community-acquired respiratory tract infections. Fifteen participating U.S. medical centers submitted clinically significant isolates of Haemophilus influenzae, MoraxeeUa (BranhameUla) isolates, 1 (0.2%) was penicillin resistant, while 3.8% were relatively resistant to penicillin, 4.5% were resistant to trimethoprim-sulfamethoxazole, 2.3% were resistant to tetracycline, 1.2% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
148
4
6

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(171 citation statements)
references
References 32 publications
13
148
4
6
Order By: Relevance
“…Non-ß-lactamase-mediated ampicillin resistance was not detected among the H. influenzae strains studied. This is in agreement with numerous previous surveillance studies, which have indicated that such observations remain uncommon (11,13,14). It has been postulated that BLNAR is associated with altered penicillin-binding proteins (PBPs) and might be due to a lower virulence of strains with abnormal PBPs (13,16,26).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Non-ß-lactamase-mediated ampicillin resistance was not detected among the H. influenzae strains studied. This is in agreement with numerous previous surveillance studies, which have indicated that such observations remain uncommon (11,13,14). It has been postulated that BLNAR is associated with altered penicillin-binding proteins (PBPs) and might be due to a lower virulence of strains with abnormal PBPs (13,16,26).…”
Section: Discussionsupporting
confidence: 83%
“…Similar results have also been obtained in a collaborative study conducted in the US during the 80s and in São Paulo during the 90s (20,21). In Finland and in South Africa the overall rate of ß-lactamasemediated ampicillin resistance in H. influenzae was 10% (11,22,23).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…La resistencia a eritromicina y a cloranfenicol se encontró en pocos casos, lo que concuerda con datos de Estados Unidos y Australia (32,33). Por tanto, parece ser que la resistencia a estos dos agentes no es todavía un problema en nuestro medio si se compara con paí-ses como Francia, donde la resistencia a los macrólidos llega a 29% (34) o, como España, donde se ha hallado 30% de resistencia al cloranfenicol (35).…”
Section: Discussionunclassified